Melatonin-Mediated Colonic Microbiota Metabolite Butyrate Prevents Acute Sleep Deprivation-Induced Colitis in Mice - Ting Gao (MDPI AG, 2021)
Radical cure colitis is a severe public health threat worldwide. Our previous studies have confirmed that melatonin can effectively improve gut microbiota disorder and mucosal injury caused by sleep deprivation (SD). The present study further explored the mechanism whereby exogenous melatonin prevented SD-induced colitis. 16S rRNA high-throughput sequencing and metabolomics analysis were used to explore the correlation between SD-induced colitis and intestinal microbiota and metabolite composition in mice. Fecal microbiota transplantation (FMT) and melatonin or butyrate supplementation tests verified the core role of gut microbiota in melatonin-alleviating SD-induced colitis. Further, in vitro tests studied the modulatory mechanism of metabolite butyrate. The results demonstrated that SD leads to reductions in plasma melatonin levels and colonic Card9 expression and consequent occurrence of colitis and gut microbiota disorder, especially the downregulation of Faecalibacterium and butyrate levels. The FMT from SD-mice to normal mice could restore SD-like colitis, while butyrate supplementation to SD-mice inhibited the occurrence of colitis, but with no change in the plasma melatonin level in both treatments. However, melatonin supplementation reversed all inductions in SD-mice. In intestinal epithelial cells, the inflammatory ameliorative effect of butyrate was blocked with pretreatments of HDAC3 agonist and HIF-1α antagonist but was mimicked by GSK-3β and p-P65 antagonists. Therefore, the administration of MLT may be a better therapy for SD-induced colitis relative to butyrate. A feasible mechanism would involve that melatonin up-regulated the Faecalibacterium population and production of its metabolite butyrate and MCT1 expression and inhibited HDAC3 in the colon, which would allow p-GSK-3β/β-catenin/HIF-1α activation and NF-κB/NLRP3 suppression to up-regulate Card9 expression and suppress inflammation response.